Improving the nutritional content of apple pomace using biological treatments as a nonconventional broiler feed - Irfan H Djunaidi; Yuli Frita Nuningtyas; Muharlien Muharlien (Faculty of Animal Science, Universitas Brawijaya, 2020)
This study was aimed to evaluate apple pomaces using fermentation and enzymatic technology (Aspergillus niger and glucanase enzymes). Treatments in this research were used enzymatic technology (T1) and fermentation technology (T2) and the second factor of the level of enzyme used Aspergillus niger processing: without Aspergillus niger (L0), 0.2% Aspergillus niger (L1), 0.4% Aspergillus niger (L2) and 0.6% Aspergillus niger (L3) and treatment used Glucanase enzyme: without Glucanase (L0), 0.2% Glucanase (L1), 0.4% Glucanase (L2) and 0, 6% Glucanase (L3). Data analysis used nested using a Completely Randomized Design. Based on the results of the study shows that fermentation technology using 0.6% glucanase gives better feed quality compared to the treatment using Aspergillus niger.